Vascular Leiomyoma Presenting as Anterior Knee Pain (Case Report) - Aydın, Elçin (J Belg Soc Radiol, 2016)
Vascular leiomyomas or angioleiomyomas are rare benign solitary smooth muscle tumors that origin usually in the extremities. Most of these tumors are composed of venous vessels. Here in, we report a rare case of subcutaneous vascular leiomyoma of the right knee of a 38 year old woman who was presented with recurrent anterior right knee pain and soft tissue swelling. Clinical findings, magnetic resonance imaging and histopathologic findings of the tumor is discussed. Leiomyomas are not mostly considered in the differential diagnosis by radiologist due to its rarity. Typical imaging and clinical findings of a tumor is an important clue for an accurate and early diagnosis.